2015
DOI: 10.1007/s10479-015-1912-7
|View full text |Cite
|
Sign up to set email alerts
|

Priority control of berth allocation problem in container terminals

Abstract: This paper presents a decision support system for the core problem of berth allocation decision in a container terminal. The allocation of berths to the calling vessels is complex with the fact that different service level requirements are required for different vessels. Terminal managers demand for effective decision support systems that would aid them with the allocation problem considering service priorities. Consequently, this study provides a DSS, built by a dynamic discrete-event simulation model embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…The pioneering study considering continuous BAP is Imai et al (2005). Recently, it has been still in focus with the variants studied in Ursavas (2015), , Mauri et al (2016), etc. Moreover, in some related works, the quay is partitioned in a hybrid approach where some vessels might only fit in multiple berths (e.g.…”
Section: Bap Literaturementioning
confidence: 99%
“…The pioneering study considering continuous BAP is Imai et al (2005). Recently, it has been still in focus with the variants studied in Ursavas (2015), , Mauri et al (2016), etc. Moreover, in some related works, the quay is partitioned in a hybrid approach where some vessels might only fit in multiple berths (e.g.…”
Section: Bap Literaturementioning
confidence: 99%
“…According to the above-mentioned, research on scientific and professional literature has been expanded upon, in the use of DS in maritime spatial planning, and it has been noted that most of the research was related to DS usage in the berth allocation problem [27][28][29][30][31][32][33][34][35][36]. None of these authors conducted studies in which all affected groups (government, experts, and users) were involved in the strategy selection, and none of them gave a solution for the spatial plan design for the development of anchorage capacities with the approach of DSC as a proven high quality "tool" for decision-makers dealing with this issue.…”
Section: Discussionmentioning
confidence: 99%
“…This can be coped with the fact that most countries have just started to apply MSP. The application of DS in MSP has been found in papers dealing with the protection of environment, ecology, biodiversity, coastal, and seabed habitat features [19][20][21][22][23][24][25][26], marine traffic [27][28][29][30][31][32][33][34][35][36], anchorage planning strategy [37], and site identification (selection) [38][39][40]. It can be concluded that most of the papers, in which DSS is used in the planning of various activities in MSP, are based on ecological issues, and on the issue of regulating traffic within maritime industrial ports, but not with the development of spatial plans, and especially not with plans related to the construction of anchorages as a civil engineering problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, terminal operators have different preferences regarding the service priority. For example, it was reported that most of the Japanese terminals preferred ships with larger container volume being served first while ships with smaller container volume were favored in Dalian container terminal of China [5,6,22,[30][31][32] Ursavas [32] extended the work of BAP on priority considerations by proposing a decision support system for determining priority controls based on simulation optimization.…”
Section: Service Priority Considerationmentioning
confidence: 99%